2022
DOI: 10.3390/f13122157
|View full text |Cite
|
Sign up to set email alerts
|

Total Stem Biomass Estimation Using Sentinel-1 and -2 Data in a Dense Coniferous Forest of Complex Structure and Terrain

Abstract: Accurate above-ground biomass (AGB) estimation across multiple spatial and temporal scales is essential for mitigating climate change and optimizing forest management strategies. The aim of the present study was to investigate the potential of Sentinel optical and Synthetic Aperture Radar (SAR) data in reliably estimating the plot-level total stem biomass (TSB), which constitutes the dominant material among the different tree components of AGB (stem, branches, and leaves). The study area was located in a dense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 84 publications
0
2
0
1
Order By: Relevance
“…As shown in Figure 5b, NDII emerged as the most critical variable, and we found that the third principal component factor (PCA3) contained more biomass-related information. Backscatter coefficient VH was found to be more suitable for AGB inversion compared to VV [70]. Features such as ARVI, b7, CON, DIS, DVI, HO, NDII, NDVI, OSAVI, PCA3, SAVI, SR, VH, and VH/VV contributed significantly, and will thus be used as input features for subsequent Tent_ASO_BP model development and AGB prediction.…”
Section: Variable Selection Resultsmentioning
confidence: 99%
“…As shown in Figure 5b, NDII emerged as the most critical variable, and we found that the third principal component factor (PCA3) contained more biomass-related information. Backscatter coefficient VH was found to be more suitable for AGB inversion compared to VV [70]. Features such as ARVI, b7, CON, DIS, DVI, HO, NDII, NDVI, OSAVI, PCA3, SAVI, SR, VH, and VH/VV contributed significantly, and will thus be used as input features for subsequent Tent_ASO_BP model development and AGB prediction.…”
Section: Variable Selection Resultsmentioning
confidence: 99%
“…Газрын дээрх биомасс (ABG) нь ойн нийт биомассын 80 орчим хувийг эзэлдэг ба ойн төлөв байдлыг илэрхийлэх гол үзүүлэлт юм [4,5].…”
Section: оршилunclassified
“…Compared to a process that does not consider or does not adequately consider topographic correction [38,61], radiative terrain correction for PolSAR data is a combination of three aspects of terrain correction [50,59,60,62,63], of which the most comprehensive radiometric terrain correction (RTC) process is one that includes all three aspects (POAC, ESAC, and AVEC) [43,64,65]. However, in terms of ESAC, the cross-sectional area of radar scattering is only applicable to a single scattering target (the target object is smaller than the irradiation range), and the scattered signal of the resolution unit for distributed scatterers (such as forests) is the result of coherent superposition of the scattered signal of each single scatterer, so the backscattering coefficient is commonly used to describe the scattering ability of ground objects based on statistical methods.…”
Section: Introductionmentioning
confidence: 99%